Viscometric Study of Bis(cinnamaldehyde) and Their Schiff Base Polymers in DMF and THF Solution at 30 ºC - Shah, Ambreen; A. Shah, Asif (Asian Journal of Chemistry, 2013)
Viscometric parameter is a simplest method to determine molecular shape, size and weight. Bis(cinnamaldehyde) and their Schiff base polymeric solutions were prepared in DMF and THF at 30 ºC, to investigate viscometric study by dilute solution viscometry method. The intrinsic viscosity and viscometric constants of these solutions were calculated by six different equations such as Huggins, Kramer, Martin and Schulz-Blaschke equations by graphic extrapolation and Solomon-Ciuta, Deb-Chantterjee equations through a single point determination, which represents the advantage of being a faster method. The thermodynamic parameters e.g., DG, DS and DH, were also calculated by equation related with dilute solution viscometry method. The molecular mass of polymers was determined by applying Mark-Howwink-Sakurada equation. The results obtained that the single point determination can be applied and Deb-Chantterjee equation showed to be the most appropriate for those calculations.